EFEKTIVITAS PEMUNGUTAN PAJAK KENDARAAN BERMOTOR - Bashiruddin Ahmad; Buyung Romadhoni; Muhammad Adil (Universitas Muhammadiyah Makassar, 2020)
Generally this research aiming to know the effectiveness of vehicle tax collection in Shared Office : One Roof System Office located in Gowa Districts. This research use descriptive research method that objectively give the correct description or explanation related to the real condition of the research object. The data collection techniques that is used are interview and observation. in shared office : One Roof System Office in GowaDistricts is already effective in vehicle tax collection. Although, there are still many obstacles were encountered. One of it is the lack of awareness of the citizens to pay the tax on time which result in taxpayers pile up the vehicle tax payments. But, in payment procedure of vehicle tax is already good because it does not take a long time in vehicle tax paymentmatter.